Proposals for Upper Limits of Safe Intake for Arginine and Tryptophan in Young Adults and an Upper Limit of Safe Intake for Leucine in the Elderly. Issue 12 (9th November 2016) - Cynober, Luc; Bier, Dennis M; Kadowaki, Motoni; Morris, Sidney M; Elango, Rajavel; Smriga, Miro
Abstract: On the basis of research presented during the 9th Amino Acid Assessment Workshop, a No Observed Adverse Effect Level (NOAEL) for diet-added arginine (added mostly in the form of dietary supplements) of 30 g/d and an upper limit of safe intake (ULSI) for diet-added tryptophan (added mostly in the form of dietary supplements) of 4.5 g/d have been proposed. Both recommendations apply to healthy young adults. The total dietary leucine ULSI proposed for elderly individuals is 500 mg · kg −1 · d −1 . All 3 recommendations are relevant only to high-quality amino acid–containing products with specifications corresponding to those listed in the US Pharmacopeia . Because the above amino acids are extensively utilized as dietary supplements for various real or perceived benefits, such as vasodilation, spermatogenesis, sleep, mood regulation, or muscle recovery, the above safety recommendations will have an important impact on regulatory and nutritional practices.